Temporal variations in the incompatible trace element systematics of Archean TTGs: Implications for crustal growth and tectonic processes in the early Earth - Sotiriou, Paul; Polat, Ali; Windley, Brian; Kusky, Timothy (Earth-Science Reviews, 2023)
In this study, we applied classification and tectonic setting diagrams, N-MORB-normalised trace element and incompatible element temporal variation diagrams, Nb/Nb*, Pb/Pb*, La/Smn, La/Nbn, Th/Nbn and Pb/Cen ratios and field-structural relationships to Archean tonalites, trondhjemites and granodiorites (TTGs) and Phanerozoic arc-generated TTGs. Geochemical analyses were compiled from the literature to elucidate how Archean continental crust formed, whether plate tectonics operated in the Archean, if this Archean form of plate tectonics resembled modern-style plate tectonics, and when plate tectonics commenced in the early Earth. The Archean TTGs used for this study were not noticeably influenced by alteration or crustal contamination; therefore, their geochemistry is indicative of their original juvenile sources and the tectonic environments in which they were generated. These rocks are predominantly calcic to calc-alkalic and magnesian granitoids derived from low-K mafic/tholeiitic sources. Most Archean TTGs have high La/Ybcn and Sr/Y ratios and low Ybcn values and Y contents characteristic of adakites and formed by partial melting of subducting oceanic crust or the lower arc crust. However, some Archean TTGs resemble modern arc andesites, dacites and rhyolites that have low La/Ybcn and Sr/Y ratios and high Ybcn values and Y contents and formed by fractional crystallisation of basaltic magmas derived from partial melting of the sub-arc mantle wedge. Archean TTGs overlap with their Phanerozoic counterparts and mainly plot in the arc fields of tectonic setting discrimination diagrams. The N-MORB-normalised trace element patterns of Archean TTGs from well-studied cratons bear a striking resemblance to those of TTGs from modern active arcs (e.g., Izu-Bonin-Mariana, Andean) and from older Phanerozoic arcs (e.g., Sierra Nevada, Gangdese), consistent with their formation in arcs. The temporal variations in the trace element geochemistry of Archean TTGs underwent a noticeable change on a global scale at ca. 3500–3200 Ma. The vast majority (99%) of Archean TTGs have Nb/Nb* and Pb/Pb* anomaly ratios of <1 and >1, respectively, and are interpreted to have formed in arc settings; the remainder had non-arc origins. The La/Smn, La/Nbn, Th/Nbn and Pb/Cen ratios of these TTGs suggest that 99% of these rocks formed in supra-subduction zone settings, namely arcs, forearcs and back-arcs, the remainder being derived from mantle plumes and mid-ocean ridges. This study suggests that throughout the Archean TTGs were generated in subduction zones by modern-style plate tectonic processes, beginning in the Hadean (>4000 Ma). TTGs began to form in intra-oceanic arcs at ca. 4020 Ma prior to a global-scale switch to Andean-style continental arc magmatism at ca. 3500–3200 Ma, which led to the genesis of TTGs in continental arcs worldwide in the Paleoarchean. Modern-style plate tectonic processes predominantly contributed to the formation of Archean continental crust. As such, global-scale vertical tectonic processes did not play a significant role in the formation of Archean continental crust. Most plutons are emplaced vertically into the crust, as exemplified by modern arcs. Vertical tectonic processes are locally observed in Archean cratons, leading many researchers to erroneously conclude that vertical tectonic processes were predominant in the early Earth.
CRIS-Team Scopus Importer:2023-01-06
Keywords: Archean tectonics; Early Earth processes; Incompatible trace element systematics; TTG petrogenesis; TTGs